Effects of site, cerebral perfusion and degree of cerebral artery stenosis on cognitive function. Issue 3 (3rd February 2021) - Xie, Binbin; Liu, Yidan; Wu, DongMei; Li, Gongbo; Chen, Taosong; Xiao, Shufang; Yang, Jing; Li, Jiamin; Li, Xiaofeng
Abstract : Objective: To investigate the effects of site, cerebral perfusion and degree of cerebral artery stenosis (CAS) on cognitive function. Methods: A total of 57 patients with CAS and 53 controls from January 2019 to December 2019 were included. The former group was further divided into different subgroups according to the site, cerebral perfusion and degree of CAS. A series of neuropsychological tests were performed to evaluate the cognitive domains (such as memory, executive function, psychomotor speed, etc.). Rank sum test, t test, Chi-square test and analysis of variance were used for data analysis. Spearman correlation analysis was used to examine the relationship between the site, cerebral perfusion and degree of CAS and all tests' scores. Results: For patients with CAS who have decreased cerebral perfusion, their global cognitive function, memory, psychomotor speed, executive function and frontal lobe function were significantly impaired (all P < 0.05). There was a significant decrease in global cognitive function, psychomotor speed, memory, executive function and frontal lobe function in patients with anterior circulation stenosis (all P < 0.05). Moderate and severe CAS impaired subjects' global cognitive function, memory, psychomotor speed, executive function and frontal lobe function (all P < 0.05). There was a correlation between the site, cerebral perfusion, the degree of CAS and cognitive function. Conclusion: Global cognitive function, memory, psychomotor speed, frontal lobe function and executive function are impaired in patients with CAS, especially in those with anterior circulatory stenosis, moderate to severe stenosis and low cerebral perfusion. See Video Abstract, http://links.lww.com/WNR/A613 . Abstract : Supplemental Digital Content is available in the text.